Design of Cross-bureau Data Transmission Scheme for Locomotive RemoteMonitoring and Diagnosis System - ZHAO Chao; HU Weimin; WU Zijian; ZHU Qianliu (Kongzhi Yu Xinxi Jishu)
Based on the fact that quite a number of locomotives are used across different locomotive depots while their data is locally downloaded in servicing yard, two schemes of cross-bureau locomotives data transmission were proposed in this paper so as to solve the problem that locomotives stationed outside depot cannot across back the CMD (Chinese locomotive remote monitoring and diagnosis system of locomotive system) data. This paper analyzed their respective advantages and disadvantages, and proposed to adopt the data "from section to head office" turn-back scheme based on the existing network conditions. A data turn-back synchronization system is built by using FTP service and network communication technology, which solves the problem of data return of locomotive from stationed depot to belonged depot.